Effectiveness of Problem-Based Learning with Diorama Media on Students’ Creative Thinking in IPAS at SDN Kalicari 02 Semarang - Alfiyah Nurul Fuadah; Khusnul Fajriyah; Intan Rahmawati (Walidem Institute and Publishing, 2025)
Objective: This study aims to examine the effectiveness of the Problem-Based Learning (PBL) model assisted by a food chain tower diorama in enhancing the creative thinking abilities of fifth-grade students in the Natural and Social Sciences (IPAS) subject at SDN Kalicari 02 Semarang. Theoretical framework: Theoretically, creative thinking is an essential 21st-century skill that allows students to generate innovative ideas and solutions. PBL provides a contextual, student-centered framework that promotes active inquiry, collaboration, and higher-order thinking. Literature review: Previous research has shown that PBL models, when integrated with visual learning media, can significantly improve learning outcomes and student engagement. Methods: This study employed a quantitative approach using a pre-experimental one-group pretest-posttest design. The research subjects consisted of 27 fifth-grade students. The research instrument was a set of 10 open-ended essay questions that had passed tests of validity, reliability, difficulty level, and discrimination index. Data were collected through pretest and posttest assessments to measure students' creative thinking abilities before and after the intervention. Results: The results demonstrated a significant improvement in student performance. The average pretest score of 72.78 increased to 87.22 in the posttest. A paired sample t-test revealed a significance value of 0.000 (< 0.05), indicating a statistically significant difference between the pretest and posttest scores. Moreover, the N-Gain score averaged 0.5434 (54.34%), which falls into the moderate category, suggesting that the learning intervention was effective in improving creative thinking skills. Implications: The findings imply that the combination of the PBL model with diorama media provides a powerful tool for stimulating creativity in primary school students, particularly in understanding abstract scientific concepts such as food chains. Novelty: This study’s novelty lies in the integration of a concrete visual diorama with problem-based instruction in the IPAS context, which has been less explored in elementary education research. It serves as a reference for teachers seeking innovative strategies to foster creativity through contextual and student-centered learning.